2015
DOI: 10.1105/tpc.15.00208
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of the Network of Primary Metabolism and Their Relationships to Plant Performance in a Maize Recombinant Inbred Line Population

Abstract: Deciphering the influence of genetics on primary metabolism in plants will provide insights useful for genetic improvement and enhance our fundamental understanding of plant growth and development. Although maize (Zea mays) is a major crop for food and feed worldwide, the genetic architecture of its primary metabolism is largely unknown. Here, we use high-density linkage mapping to dissect large-scale metabolic traits measured in three different tissues (leaf at seedling stage, leaf at reproductive stage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
163
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(184 citation statements)
references
References 78 publications
11
163
1
Order By: Relevance
“…The variation of almost all PAs in this study was controlled by a few loci with large effects, which is in accordance with a handful of previous studies on specialized metabolites and distinct from those described for QTLs of primary traits (Fridman et al, 2004;Rowe et al, 2008;Schauer et al, 2008;Chan et al, 2010;Joseph et al, 2013;Alseekh et al, 2015;Wen et al, 2015), for which a large number of minor loci are usually detected. Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The variation of almost all PAs in this study was controlled by a few loci with large effects, which is in accordance with a handful of previous studies on specialized metabolites and distinct from those described for QTLs of primary traits (Fridman et al, 2004;Rowe et al, 2008;Schauer et al, 2008;Chan et al, 2010;Joseph et al, 2013;Alseekh et al, 2015;Wen et al, 2015), for which a large number of minor loci are usually detected. Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, large-scale metabolic trait QTL mapping was also performed in the same RIL population in different tissues including leaf (Wen et al, 2015). A common QTL hotspot was observed on chromosome 10 (Supplemental Fig.…”
Section: Qtl Analysismentioning
confidence: 99%
“…With the rapid development of next-generation sequencing and high-density single-nucleotide polymorphism (SNP) genotyping technologies, linkage mapping and genome-wide association studies have been used widely to dissect the genetic architecture of agriculturally important traits in commercial maize (Buckler et al, 2009;Kump et al, 2011;Tian et al, 2011;Li et al, 2013;Wen et al, 2014Wen et al, , 2015. Many genes and variants underlying agriculturally important traits have been discovered in crops (Kesavan et al, 2013;Zuo and Li, 2013;Martinez et al, 2016).…”
mentioning
confidence: 99%